Challenges following CRS and HIPEC surgery in cancer patients with peritoneal metastasis: a comprehensive review of clinical outcomes - Karimi, Mehdi; Shirsalimi, Niyousha; Sedighi, Eshagh (Frontiers in Surgery, 2024)
Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) are a pair of relatively modern therapeutic surgical methods in advanced cancerous patients with peritoneal metastasis (PM). The goal of CRS + HIPEC is treatment or to improve survival outcomes, which are linked to high morbidity side effects and complications, even with their possible advantages. Surgical-related, chemotherapy-related, anesthetic-related, gastrointestinal, organs and systemic complications are the categories into which complications are separated according to frequency, risk factors, and effect on patient outcomes. In this narrative review of the literature, the side effects and complications of HIPEC + CRS in cancer patients with PM are examined. The present knowledge on the incidence, frequency, kinds, and risk factors of acute complications following CRS + HIPEC is summarized in this study. This review emphasizes the need for careful patient selection criteria, precise surgical technique, and thorough intraoperative care to reduce or manage these risks. Moreover, it highlights the need for interdisciplinary collaboration in treating these patients. This study aims to know these complications, improve clinical practice, and guide future studies to increase the safety and efficacy of CRS + HIPEC in treating metastatic colorectal cancer.